2021
DOI: 10.1108/ijbm-06-2021-0272
|View full text |Cite
|
Sign up to set email alerts
|

I won't touch money because it is dirty: examining customer's loyalty toward M-payment

Abstract: PurposeSeveral industries including banking are booming because of COVID-19. However, it is still unknown whether this growth is momentary or permanent in nature. Hence, this study aims to identify the role of health-related concerns and trust as stimuli on M-payment loyalty.Design/methodology/approachData were collected through Google Forms from 431 participants. Subjects were M-payment users. The hypothesized model was tested using structural equational modeling.FindingsResults of the study indicate that per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 119 publications
0
43
0
Order By: Relevance
“…We used a quantitative method to test the proposed model (Figure 1) to examine the Indian shopper’s online impulsive shopping behavior using the TAM model. We used a convenience sampling method to recruit the respondents because of the nonavailability of an online shopper’s details in the digital realm (Goel et al , 2021; Mehta et al , 2022). Prior research has shown that in the case of a large sample population, the convenience sampling approach is advised to gather data quickly (Goel et al , 2021; Patel et al , 2020; Rafdinal and Senalasari, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used a quantitative method to test the proposed model (Figure 1) to examine the Indian shopper’s online impulsive shopping behavior using the TAM model. We used a convenience sampling method to recruit the respondents because of the nonavailability of an online shopper’s details in the digital realm (Goel et al , 2021; Mehta et al , 2022). Prior research has shown that in the case of a large sample population, the convenience sampling approach is advised to gather data quickly (Goel et al , 2021; Patel et al , 2020; Rafdinal and Senalasari, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We used a convenience sampling method to recruit the respondents because of the nonavailability of an online shopper’s details in the digital realm (Goel et al , 2021; Mehta et al , 2022). Prior research has shown that in the case of a large sample population, the convenience sampling approach is advised to gather data quickly (Goel et al , 2021; Patel et al , 2020; Rafdinal and Senalasari, 2021). We collected primary data via a structured questionnaire, which started in the first week of May and will end in the third week of July 2021.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations